Characteristics and outcomes of hospitalized adults with COVID-19 in Nepal: a multicenter, prospective cohort study - Ashok Chaudhary; Uday Narayan Singh; Pramod Paudel; Niresh Thapa; Kamal Khadka; Prameshwar Kumar Sah; Sher Bahadur Kamar; Jagadish Joshi; Kamar Hasan Ansari; Shree Ram Tiwari; Sarbesh Sharma; Sanjay Kumar Jaiswal; et al. (Journal of Infection in Developing Countries)
Introduction: There is limited data on clinical course and outcomes of hospitalized adults with COVID-19 in Nepal. Thus, it is imperative to characterize the features of this disease in the domestic context.